Climate change Action: IoT-Driven Mitigation and Resilient Infrastructure - Yadav, Saurav; Kesharwani, Riddhi (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2025)
Climate change presents a pressing global challenge, requiring urgent action on both mitigation and adaptation fronts. This research examines the multifaceted impacts of climate change on ecosystems and human societies. It explores innovative technologies and sustainable practices to reduce greenhouse gas emissions and mitigate the severity of climate change. Additionally, the study investigates strategies to adapt to the inevitable consequences of climate change, such as sea-level rise and extreme weather events. By analyzing the interplay between mitigation and adaptation, this research aims to contribute to the development of effective policies and solutions to address this complex global issue.